Peranan Fonologi Dalam Pengajaran Bahasa Indonesia di Tingkat SD - Sari, Tifanny Dwi Permata; Siagian, Irwan (Jurnal Ilmiah Wahana Pendidikan, 2024)
The study aims to analyze the importance of phonology teaching in the context of learning Indonesian language at the level of elementary school. (SD). Phonology is an important aspect in the linguistic study of sound systems in a language. Effective phonology teaching can help students in recognizing and producing Indonesian sounds correctly, understanding changes in sounds, as well as enhancing their ability in distinguishing the meaning of words through differences in sounds. Effective teaching methods in phonological aspects include introduction and practice in speech, selection of words that contain specific changes in sounds, as well as understanding listening and using the Indonesian language. In addition, the use of technology can enrich student learning experience by listening to examples of good and correct Indonesian language voices. An emphasis on phonology teaching can also help students overcome mistakes in speaking and increase confidence in communicating in Indonesian. By gaining a good understanding of phonology, students can avoid common mistakes, teachers need to have a profound understanding of the Indonesian language sound system as well as effective teaching strategies to overcome students’ difficulties in understanding and mastering phonography.